2009
DOI: 10.1093/protein/gzp028
|View full text |Cite
|
Sign up to set email alerts
|

Towards temperature-dependent coarse-grained potentials of side-chain interactions for protein folding simulations. I: Molecular dynamics study of a pair of methane molecules in water at various temperatures

Abstract: By means of molecular dynamics simulations of a pair of methane molecules in a TIP3P periodic water box with the NVT scheme at six temperatures and, additionally, the NPT scheme at three temperatures ranging from T = 283 to 373 K, we determined the potential of mean force (PMF) of pairs of interacting methane molecules in water as functions of distance between the methane molecules. The PMFs converge to a single baseline only for r> 11 A at all temperatures. The curves of the dimensionless PMF obtained at diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
11
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 36 publications
6
11
0
Order By: Relevance
“…If, for the purposes of comparison, the w AA (r) values were matched at solvent-separated radii, then the Pangali et al results show stronger contact hydrophobic attractions than does the PC theory, qualitatively in agreement with the present work. Recent molecular dynamics simulations for Xe(aq) or CH 4 (aq) pairs (42)(43)(44) agree qualitatively with the present results and thus support this conclusion. Inclusion of longer-ranged attractive interactions, i.e., London dispersion interactions, can change these B 2 values and trends depending on the balance of solute-solute and solute-water interactions (11,16,18).…”
Section: Resultssupporting
confidence: 91%
“…If, for the purposes of comparison, the w AA (r) values were matched at solvent-separated radii, then the Pangali et al results show stronger contact hydrophobic attractions than does the PC theory, qualitatively in agreement with the present work. Recent molecular dynamics simulations for Xe(aq) or CH 4 (aq) pairs (42)(43)(44) agree qualitatively with the present results and thus support this conclusion. Inclusion of longer-ranged attractive interactions, i.e., London dispersion interactions, can change these B 2 values and trends depending on the balance of solute-solute and solute-water interactions (11,16,18).…”
Section: Resultssupporting
confidence: 91%
“…The results of the study reported in this work as well as those of our previous work 13 strongly suggest that the dimensionless potentials of mean force of pairs of nonpolar solutes depend weaker on temperature in the region of contact minimum than the potential of mean force. This is consistent with the fact that hydrophobic association as an entropy-driven phenomenon.…”
Section: Discussionsupporting
confidence: 85%
“…In these studies, diverse methodologies and water models were used for PMF determination, namely, simulations of 8 solute molecules in a periodic box with TIP3P, TIP4P, TIP5P, SPC, or SPCE water and direct calculation of solute pair-correlation function, 1112 thermodynamic integration and the SPC water model, 9 and the particle-insertion method and the TIP4P water model. 10 Recently, 13 we carried out molecular dynamics simulations for a pair of interacting methane particles at different temperatures in NVT or NPT protocols in TIP3P water model. 14 Based on our MD results, we determined the potential of mean force and dimensionless potential of mean force curves.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PMF is one of the free-energy properties with which to calculate the physicochemical properties of the systems studied. The calculated PMFs can subsequently be used to compute measurable physicochemical characteristics of the systems studied, such as, for example, association constants, 2325 and are also suitable when direct experiment is inapplicable (for example to study hydrophobic association 26,27 ) or to lower the cost of experiment. 2830 The PMFs can also be used to determine the preferred mode of interaction of the molecules or groups under study in water.…”
Section: Introductionmentioning
confidence: 99%